Socialization of Vegetable Waste Processing into Eco-Friendly Fish Pellets at SMK Muhammadiyah 7 Gondanglegi - Rahmawati, Istiqomah; Ansori; Arie Setiawan, Felix; Palupi, Bekti; Fachri, Boy; Rizkiana, Meta; Mumtazah, Zuhriah; Kharisma Yolanda Putri, Ditta; Dwi Lestari, Fitria; Naufal Nizaar Aziz, Mohamad; Pramasta, Ady (Jurnal Inovasi Sains dan Teknologi Untuk Masyarakat, 2026)
Vegetable waste is often discarded without further processing, which can lead to environmental pollution. In fact, this waste still contains 12.64%–23.5% crude protein and 20.76%–29.18% crude fiber, which can be repurposed into an environmentally friendly, value-added product: fish pellets. The lack of understanding regarding this waste poses a challenge, necessitating alternative solutions. This outreach method serves as an educational solution to enhance understanding of the potential of vegetable waste as a raw material for fish pellets. The outreach activity was conducted at SMK Muhammadiyah 7 Gondanglegi and was attended by students from various departments. The implementation stages included preparation, outreach, and evaluation. During this activity, participants were provided with materials on the benefits of vegetable waste and the steps for processing it into fish pellets. A question-and-answer session followed this to allow participants to explore the material in greater depth. The results of this activity have tangibly improved participants' understanding of processing vegetable waste into fish pellets. Participants played an active role and participated enthusiastically in this activity, creating a positive impact on both the participants and the school. Consequently, this activity can be further developed with the school's support to ensure the program's sustainability.